(untitled) (Anclajes, 2019)
The purpose of this article is to comprehensively approach the current state of research objects in the Argentinean academic literary journals. Our methodological proposal consists of the use of tools developed in the digital humanities field to carry out a distant reading that allows us to have a more encompassing and federal vision of the field according to its general guidelines and thematic recurrences. With this purpose, we take as a corpus a series of digital publications of 2014 and 2015, linked to literary studies in Argentine universities, to obtain a mapping of the dominant interests and approaches. In general terms, we seek to generate a first approximation and input that favors dialogue between investigations and objects in common.